MITOLOGI PEMENTASAN WAYANG SAPUH LEGER DALAM ESTETIKA HINDU - I Nengah Juliawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Wayang (puppet) is a relic of the community life sector which was condensed because it was sacred or considered sacred. the tradition of sapuh leger puppet show is a cultural heritage of Balinese life which is traditional and considered sacred, so it includes wali (part of the ceremony) held for religious ceremonies (manusia yajna), namely for children/people born in wuku wayang.Tumpek Wayang is one of the puppets Hindu aesthetic day in Bali because it is believed in the Tumpek Wayang is a manifestation of Sang Hyang Iswara so that for his analysis and efforts humans are able to be creative in realizing Aikyam, Ciwam, Sundaram. The ritual activity as a form of gratitude for Sang Hyang Taksu, which is often symbolized by the shadow puppet ceremony, because it contains various elements of art or total theater, in this art, all the existence and essence of the arts have been included. The meaning of the Tumpek Wayang, As we know life in the world is always covered by two forces called Rwa Bineda, which of course exist on the side of human life, by reflecting on tattwa, religious philosophy is able to bring human life to be more dignified. Because the teachings or philosophies of religion will be able to enlighten the mind which will also be able to create one's morality for the better.Keywords: Teacher, Professionalism, Quality of Education